Assessing Trends and Decomposing Change in Nonresponse Bias: The Case of Bias in Cohort Distributions. (February 2019) - Gummer, Tobias
Survey research is still confronted by a trend of increasing nonresponse rates. In this context, several methodological advances have been made to stimulate participation and avoid bias. Yet, despite the growing number of tools and methods to deal with nonresponse, little is known about whether nonresponse biases show similar trends as nonresponse rates and what mechanisms (if any) drive changes in bias. Our article focuses on biases in cohort distributions in the U.S. and German general social surveys from 1980 to 2012 as one of the key variables in the social sciences. To supplement our cross-national comparison of these trends, we decompose changes into within-cohort change (WCC) and between-cohort change. We find that biases in cohort distributions have remained relatively stable and at a relatively low level in both countries. Furthermore, WCC (i.e., survey climate) accounts for the major part of the change in nonresponse bias.